Characteristics of streptolysin S hemolysis. - Duncan, J L (1976)
The characteristics of hemolysis produced by streptolysin S (SLS) were investigated in rabbit erythrocytes. Treatment of erythrocytes with SLS at various temperatures prior to incubation at 37 C revealed an initial temperature-dependent interaction between toxin and the cells. No subsequent hemolysis occurred when erythrocytes were exposed to SLS at 0 to 10 C; exposure to toxin at temperatures above 10 C gradually increased the amount of hemolysis that occurred at 37 C. Very little binding of toxin to erythrocytes or their ghosts, as detected by a decrease of hemolytic activity from toxin preparations, could be demonstrated at any temperature. The release of hemoglobin after the temperature-dependent process occur at virtually the same rate at 0, 22, or 37 C. The loss of intracellular rubidium-86 (Rb) and hemoglobin from SLS-treated erythrocytes was studied. Rb+ release significantly preceded the escape of hemoglobin, suggesting that colloid-osmotic processes play a role in SLS hemolysis.